1983
DOI: 10.1254/jjp.33.829
|View full text |Cite
|
Sign up to set email alerts
|

Opposite effects of morphine on feeding and drinking in rats relative to administration time.

Abstract: Abstract-The present study was undertaken to examine how morphine changes food and water intake in non-fasted or fasted rats with different administration times. Morphine (1, 3 and 10 mg/kg) was intraperitoneally administered at 10:45 (light period) or 18:45 (dark period). Morphine increased food and water intake in non-fasted rats 2 hr after the administration during the light period, whereas the total daily intakes were decreased. In contrast, morphine decreased food and water intake in non-fasted rats durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
0

Year Published

1984
1984
1994
1994

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…Such an effect has been previously reported for morphine (Leshem 1981 a;Kunihara et al 1983), where a triphasic effect on feeding resulted in an overall reduction of intake during 24 h.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Such an effect has been previously reported for morphine (Leshem 1981 a;Kunihara et al 1983), where a triphasic effect on feeding resulted in an overall reduction of intake during 24 h.…”
supporting
confidence: 80%
“…A large body of evidence attesting to the opiates' hyperphagic influence (Grandison and Guidotti 1977;Cooper and Sanger 1984;Gold and Sternbach 1984;Morley et al 1984) has served to draw attention away from the earlier reports of morphine-induced anorexia (Frenk and Rogers 1979;Marks-Kaufman and Kanarek 1980;Sanger and McCarthy 1980;Cooper 1981;Leshem 1981a;Kunihara et al 1983). There are good reasons for this bias in favour of opiate-induced hyperphagia.…”
mentioning
confidence: 99%
“…That is, body weight loss due to cessation of morphine administration was not induced in the schedule of morphine administra tion employed in the present study, and it is unlikely that the increase in body weight in morphine-treated rats is the result of recovery from morphine withdrawal-induced body weight loss after injection of morphine at 6:00. Recently it was reported that a single dose of morphine evoked a dose-dependent change in feeding (21,22): a brief (1 hr) anorexia was followed by hyperphagia (3 hr). Therefore, the body weight increases after saline in the rats treated with morphine for 1 6 days might be the result of the hyperphagic effect of morphine.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been rarely studied that opioids such as morphine have different effects on food intake which are related to feeding con ditions or administration time (5, 6). We previously reported that in non-fasted rats, morphine increased food intake for 2 hr following the injection during the light period, but decreased it during the dark period; and in fasted rats, morphine decreased food intake regardless of adminis tration time (7). This report suggests that the two differnt effects of morphine disturb the baseline levels of feeding in naive rats; morphine could stimulate feeding when rats were in a satiated state (in non-fasted rats during the light period), whereas morphine could suppress feeding when rats were in a hungry state (in non-fasted rats during the light period and in fasted rats).…”
mentioning
confidence: 93%